On the best approximation of classes of convolutions of periodic functions by trigonometric polynomials - Serdyuk, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We present sufficient conditions for kernels to belong to the classN n * . In certain cases, this enables us to find exact values of the best approximations of classes of convolutions by trigonometric polynomials in the metrics ofC andL.